The new american desk encyclopedia - Paxson, William C.
This authoriative A-to Z guide to people, historial and contemporary events is clearly written, easy -to-date use comprohensive in scope, and completely up-to date. Its extraordinary coverage of almost every aspect of human knowledge and activity makes it the ideal reference volume for home, office or classroom special features inclde.